A Study Of Interest In A Group Of Nursery School Children As Manifested In Free Activity - Kell, Leone B. (Kansas State University, 1928)
The spontaneous activity of children, popularly called play, has been discussed since the time of Plato. Some theories of play are well known; the Schiller-Spencer theory that play results from a surplus of energy, the theory of Gross that it is a preparation for life; of Hall that it is a repetition of racial experience; of Patrick that it serves for relaxation; of Lee, who says that play is growth; and of Appleton who believes it exists because of biological necess1 ty. The theories of Spencer and Hall are doubted. 'While the remaining theories are illuminating, no one of them is complete. Since the acceptance of the theory of organic evolution we explain play in terms of structure and function; we say that it is serious and that it is an essential element of growth and development, physical, mental and moral.